FRI0144 Analysis of the Association Between Cigarette Smoking and Clinical Response to Certolizumab Pegol Treatment in Hungarian Patients with Rheumatoid Arthritis. (9th June 2015) - Szekanecz, Z.; Pulai, J.; Drescher, E.; Varga, T.; Kiss, C.; Gál, J.; Kerekes, K.; Orosz, R.; Dunkel, J.; Koncz, Ά.
Abstract : Background: Smoking is an important environmental factor affecting the development and severity of rheumatoid arthritis (RA), likely by modulating the immune system (including protein citrullination and autoantibody production). 1, 2 Smoking is associated with poor response to some anti-TNF therapies for RA. 3 However, the effect of smoking on RA patients (pts) treated with certolizumab pegol (CZP) is unknown. Objectives: To investigate the association between past/current cigarette consumption and response to CZP in Hungarian RA pts, and to report the efficacy of CZP in a real-world setting. Methods: This is a prospective, non-interventional, non-comparative, 104-week (wk) study of RA pts in Hungary, Slovakia and the Czech Republic who received CZP according to the Summary of Product Characteristics. 4 Interim data are reported for the complete Hungarian pt subset observed over 104 wks; smokers and non-smokers were included. Adverse events (AEs) and serious AEs (SAEs) were assessed to Wk104 in the Safety Set (SS; pts who received ≥1 dose CZP). Observed efficacy variables were analyzed to Wk52 in the Full Analysis Set (FAS; pts who received ≥1 dose CZP with available pack-year [PY] history at baseline [BL] and DAS28 scores at BL, Wk4, 8 or 12). Primary variable was change from BL (CFB) in DAS28(ESR) at Wk12. Secondary variables included CFB in DAS28(ESR) at Wk24 and 52. Number of cigarettes smoked/day in previous month was measured at all scheduled visits. Cigarette PY history at BL was derived from a smoking habits questionnaire; 1 PY was defined as smoking 20 cigarettes/day (1 pack) over 1 year (yr). To describe the correlation, slope parameters were estimated based on simple linear regressions with CFB in DAS28(ESR) as dependent variable and PY history and current cigarette consumption as explanatory variables. Spearman's rank correlation coefficients were also calculated. Results: SS included all 197 pts enrolled. Of 144 pts in the FAS, 75 remained on CZP at Wk104. FAS BL characteristics are presented in Table A . DAS28(ESR) scores improved from BL to Wk52 (Table B ). Slopes after regressing CFB in DAS28 scores on PY history and current cigarette consumption showed increases close to 0 (Table B ). AEs occurred in 52 pts (26.4%), SAEs in 13 pts (6.6%). 2 deaths were reported, which were not considered related to the study drug. The safety profile of CZP observed in this study was in line with the CZP label. Conclusions: CZP treatment resulted in clinical improvements in Hungarian RA pts in a real-world setting; long-term efficacy of CZP in these pts was similar to efficacy seen in the pivotal CZP studies: RAPID1 and its open-label extension. 5 There was no relevant linear relationship between past or current cigarette consumption and clinical response to CZP. References: Heliövaara M. J Rheumatol 1993;20:1830–1835; 2. Saag K. Ann Rheum Dis 1997;56:463–469; 3. Hyrich K. Rheumatology 2006;45:1558–1565; 4. European Medicines Agency. Cimzia SmPC 2014; 5. Keystone E. Ann Rheum Dis 2014;73:2094–2100 Acknowledgements: The authors acknowledge Costello Medical Consulting for writing and editorial assistance which was funded by UCB Pharma. Disclosure of Interest: Z. Szekanecz: None declared, J. Pulai: None declared, E. Drescher: None declared, T. Varga: None declared, C. Kiss: None declared, J. Gál: None declared, K. Kerekes: None declared, R. Orosz: None declared, J. Dunkel Employee of: UCB Pharma, Ά. Koncz Employee of: UCB Pharma